Application of Microalgae Assemblages’ Parameters for Ecological Monitoring in Mangrove Forest - Inyang, Aniefiok Ini; Wang, You-Shao; Cheng, Hao (Frontiers in Marine Science, 2022)
Although the relationship between biodiversity and ecological functioning is a vital issue in coastal water ecology, how this relationship is influenced by environmental conditions is still unknown. It was investigated for the dynamics of algal diversity and algal pollution indices, as well as their relationships with trophic state, in a mangrove forest along the Guangdong coast, South China. It is hypothesized that the phytoplankton alpha-diversity indices and algal pollution indices have the potential to provide a signal linking trophic state and water quality variation in the mangrove forest. The t-test showed that phytoplankton alpha-diversity indices and algal pollution indices varied significantly between the dry and wet seasons (p < 0.01 or p < 0.05). The trophic state index record confirmed that the mangrove forest was mesotrophic to eutrophic during study periods while the CCME: WQI revealed that the water quality in the forest was under poor and marginal conditions in both seasons. Multivariate analysis revealed that the dynamics of phytoplankton alpha-diversity and algal pollution indices was closely related to trophic states change and influenced by environmental conditions. The results indicated that pH, total dissolved solids, salinity, electrical conductivity, turbidity, nitrate, and phosphate were the main factors affecting algal assemblages in the mangrove forest. The indices were confirmed as a quicker, faster, and reliable approach to appropriately describe and measure the trophic state variations in the mangrove ecosystem, though an integrated approach may be required in the future.